Viral enteritis after allogeneic hematopoietic stem cell transplantation: pathogens, clinical characteristics, and outcomes - Sun, Hai-Lu; Zhao, Xiang-Yu; Mo, Xiao-Dong; Lv, Meng; Sun, Yu-Qian; Wei, Fang-Fang; Xu, Lan-Ping; Wang, Yu; Zhang, Xiao-Hui; Huang, Xiao-Jun; Zhao, Xiao-Su; Pei, Xu-Ying (Frontiers in Medicine, 2025)
Viral enteritis is a common complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, data regarding the most frequent enteric pathogens, clinical characteristics, and patient outcomes remains limited. To better characterize post-HSCT viral enteritis, we retrospectively analyzed 59 patients who underwent allo-HSCT and were diagnosised with viral enteritis based on intestinal biopsy specimens. The most frequently identified pathogens were cytomegalovirus (CMV), human herpesvirus 6 (HHV-6), and Epstein-Barr virus (EBV), accounting for 37.3%, 37.3%, and 33.9% of cases, respectively. The median time for diagnosis was 56 days post-allo-HSCT. Diarrhea and abdominal pain were the predominant symptoms. Notably, 35 patients experienced diarrhea lasting 14 days or more, with a median duration of 16 days (range: 3–57 days). Forty-five patients were diagnosed with concurrent graft-versus-host disease (GVHD) by endoscopic examination. The overall survival rates for patients with viral enteritis at 1 and 3 years were 68.7% and 58.1%, respectively. Importantly, patients with CMV enteritis had significantly poorer overall survival compared to those with other viral enteritis types (P = 0.035). In conclusion, viral enteritis is a significant complication following allo-HSCT, with CMV, HHV-6, and EBV being the most common pathogens. Early identification and management are crucial, especially for CMV enteritis which is associated with poorer outcomes.